Re-thinking Women's Sport Research: Looking in the Mirror and Reflecting Forward - Lebel, Katie; Mumcu, Ceyda; Pegoraro, Ann; LaVoi, Nicole M.; Lough, Nancy; Antunovic, Dunja (Frontiers in Sports and Active Living, 2021)
Despite decades of research and advocacy—women’s professional sports continue to be considered second class to men’s sports. The goal of this paper is to rethink how we state, present, and solve problems in women’s sport. Recognizing that varied perspectives must be considered if we are to affect true change, the wisdom of a broad stakeholder group was embraced. A three-question survey was developed to examine what key constituents believe is working in women’s sports, what they believe the salient challenges are for women’s sport, and how they would prioritize the next steps forward in the post-pandemic sport landscape. Results indicated siloed differences of opinion based upon the age and role of the stakeholder in the women’s sport ecosystem. We discuss the implications and offer recommendations as to how we as scholars might recalibrate our approach to women’s sport scholarship to maximize the impact of our research and affect change.